CAMBIO, INNOVACIÓN Y CREATIVIDAD EN LA GERENCIA PERUANA - Puell Palacios, Juan (2007)
The tendencies of the modern management are not only guided to the increment of the individual productivity of the companies, but also to the positioning of them in a competitive market through the innovation, change and creativity. The managers and the modern businessmen should design future scenarios for their organizations, for it is fundamental to bet for the change; that is to say the change should be planned, innovating products or services or creating other completely new ones. The innovation is the new paradigm of the efficient and effective organizations, and the managers should have in consideration that the innovation can be of several types: radical, incremental, original, adapted, technological, of market, of products and/or services, of process, to modulate or architectural. According to the nature of the company it should be studied meticulous and prioritarily what innovation type it requires to grow in the market and to conquer to the competition. The traditional and routine companies that don´t change or innovate their products or service, will remain out of the market and competition.